2010
DOI: 10.3233/ch-2010-1326
|View full text |Cite
|
Sign up to set email alerts
|

Slow flow of passive neutrophils and sequestered nucleus into micropipette

Abstract: In the present study, the role of the nucleus and its contribution to the deformability of the passive neutrophils was investigated. To determine the rheological properties of the nucleus and of the neutrophil itself, deformation tests on single neutrophil and sequestered nucleus have been performed by micropipette under low aspiration pressure (80 Pa = 2-3 P cr ). The stiffness of the nucleus was found to be larger than that of the neutrophil, and its viscosity was found almost ten-fold higher. A subpopulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…They performed deformation tests on the neutrophil and its nucleus using micropipette under low aspiration pressure. They observed that the nucleus plays a significant role in the mechanical and rheological behavior of the neutrophils, especially while passing through openings much smaller than their size (18). Using video observation simultaneously illuminated for fluorescence and phase contrast microscopy, Campbell et al (4) analyzed the nuclear movements of moving neutrophils in vitro.…”
Section: Passive Deformationmentioning
confidence: 99%
“…They performed deformation tests on the neutrophil and its nucleus using micropipette under low aspiration pressure. They observed that the nucleus plays a significant role in the mechanical and rheological behavior of the neutrophils, especially while passing through openings much smaller than their size (18). Using video observation simultaneously illuminated for fluorescence and phase contrast microscopy, Campbell et al (4) analyzed the nuclear movements of moving neutrophils in vitro.…”
Section: Passive Deformationmentioning
confidence: 99%
“…Hence newer methods were devised in an attempt to study large number of RBC under flow-like conditions. In contrast to RBC, micropipette studies are still commonly used to examine leukocytes; though these approaches tend not to be focused on rheological deformability [22,35,[48][49][50][51][52][53].…”
Section: Micropipette Aspirationmentioning
confidence: 99%